Flow-based systems for rapid and high-precision enzyme kinetics studies - Supaporn Kradtap Hartwell (2018)
Enzyme kinetics studies normally focus on the initial rate of enzymatic reaction. However, the manual operation of steps of the conventional enzyme kinetics method has some drawbacks. Errors can result from the imprecise time control and time necessary for manual changing the reaction cuvettes into and out of the detector. By using the automatic flow-based analytical systems, enzyme kinetics studies can be carried out at real-time initial rate avoiding the potential errors inherent in manual operation. Flow-based systems have been developed to provide rapid, low-volume, and high-precision analyses that effectively replace the many tedious and high volume requirements of conventional wet chemistry analyses. This article presents various arrangements of flow-based techniques and their potential use in future enzyme kinetics applications. © Copyright 2012 Supaporn Kradtap Hartwell and Kate Grudpan.